2020
DOI: 10.1007/s10646-020-02194-4
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms grown in aquatic microcosms affect mercury and selenium accumulation in Daphnia

Abstract: Experiments examining mercury (Hg) toxicity in Daphnia are usually conducted in highly standardized conditions that prevent the formation of biofilm. Although such standardization has many advantages, extrapolation of results to natural conditions and inference of ecological effects is challenging. This is especially true since biofilms can accumulate metals/ metalloids and play a key role in their transfer to higher trophic level organisms. In this study, we experimentally tested the effects of spontaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…de Carvalho et al also observed that the Hg present in contaminated sediments was scarcely available to the Danio rerio and Oreochromis niloticus, for there was no difference in Hg concentrations in these two fishes before and after the sediment exposure experiment . Moreover, Issa et al showed that the presence of a biofilm could significantly reduce 60–70% accumulation of inorganic Hg in Daphnia by decreasing bioavailable Hg in the aqueous phase . Such conclusion was based on the fact that Daphnia accumulated Hg(II) mainly through Hg absorption from the aqueous phase rather than from ingesting Hg-containing solid phases, e.g., biofilms and sediments …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…de Carvalho et al also observed that the Hg present in contaminated sediments was scarcely available to the Danio rerio and Oreochromis niloticus, for there was no difference in Hg concentrations in these two fishes before and after the sediment exposure experiment . Moreover, Issa et al showed that the presence of a biofilm could significantly reduce 60–70% accumulation of inorganic Hg in Daphnia by decreasing bioavailable Hg in the aqueous phase . Such conclusion was based on the fact that Daphnia accumulated Hg(II) mainly through Hg absorption from the aqueous phase rather than from ingesting Hg-containing solid phases, e.g., biofilms and sediments …”
Section: Resultsmentioning
confidence: 99%
“…16 Such conclusion was based on the fact that Daphnia accumulated Hg(II) mainly through Hg absorption from the aqueous phase rather than from ingesting Hg-containing solid phases, e.g., biofilms and sediments. 16 It was also found that the accumulation pattern of Hg in medaka differed remarkably among matrix-containing and -free treatments (Table 2). Namely, there were strong and significant correlations between THg (r = 0.960, p < 0.01) and MeHg concentrations (r = 0.930, p < 0.01) in medaka and THg amounts in matrix-free treatments (Figure S4), revealing that Hg accumulation in medaka in matrix-free treatments was dose-dependent.…”
Section: Mercury and Methylmercury In Dongmenqiao Rivermentioning
confidence: 99%
See 2 more Smart Citations